Diseño de base de datos para proyectos de grado Especialización Gestión Integrada QHSE de la Escuela Colombiana de Ingeniería Julio Garativo (2016)
The degree project is based on the design and development of a bibliographic database for the QHSE Integrated Management Specialization at the Julio Garavito Colombian School of Engineering, in such a way that a compendium of the degree works made by all the students graduated from Cohort 01 to Cohort 31.